Biotechnology patenting takes off in developing countries. (10th February 2006) - Quach, Uyen; Thorsteinsdottir, Halla; Renihan, James; Bhatt, Archana; Aesch, Zoe; Singer, Peter; Daar, Abdallah
We investigated the levels and patterns of biotechnology patenting in several developing countries by examining patents registered in the US Patent and Trademark Office (USPTO) database. The results showed, firstly, that developing countries have increased their biotechnology patenting during the period with the leading countries demonstrating inventive strengths in this field. Secondly, whereas in some countries national patenting ownership was high in others it was relatively low, which may limit the ability of the countries to harness their inventions. Thirdly, the research sector has been particularly active in patenting, especially in countries with relatively strong track records in developing biotechnology products, but industrial patenting is still limited in most of the countries studied. Finally, several of the countries we examined have a strong focus on health biotechnology compared to other types of biotechnology in their patenting rates. It remains to be seen if the increased patenting will foster biotechnology innovation.